Effects of Fiber Content and Processing Parameters on Tensile Properties of Unidirectional Long Kenaf Fiber Reinforced Polylactic-Acid Composite / Izdihar Tharazi...[et al.] - Tharazi, Izdihar; Muhamad, Norhamidi; Ismail, Nur Farhani; Md Radzi, Mohd Khairul Fadzly; Razak, Zakaria; Tholibon, Dulina; Akhtar, Majid Niaz (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Recent developments within the field of natural fiber-reinforced polymer composite have led to a renewed interest in fully biodegradable composite or green composite. Interest in using green composites is due to environmental awareness concerns as well as stringent government regulations. The study is aimed to determine the optimum percentage of fiber content for unidirectional long kenaf fiber (LKF) reinforced polylactic-acid composites. In addition, the influence of processing parameters has also been investigated but only for the optimum fiber content. The percentage of kenaf used are 10 wt% to 50 wt% prepared by film stacking method with a hot-press machine. A series of tensile tests was performed to obtain the tensile strength, including the Young’s modulus of the composite. The 40 wt% fiber composites showed tensile strength, and the Young’s modulus increased linearly to 230% and 650%, respectively. Furthermore, for 50 wt% of fiber content, tensile strength and young modulus increased linearly to 244% and 625% compare to pure polymer, respectively. It was found that better tensile properties were achieved with 50%wt fiber composites produced at a temperature of 200oC, 5MPa compression pressure and 5 minutes holding time. Applications for fabricated compoistes are in non-structural to structural with medium loads, especially in the field of aerospace, automotive, and building construction industries.